KIF18B is a Prognostic Biomarker and Correlates with Immune Infiltrates in Pan-Cancer - Qiu, Meng-jun; Wang, Qiu-shuang; Li, Qiu-ting; Zhu, Li-sheng; Li, Ya-nan; Yang, Sheng-li; Xiong, Zhi-fan (Frontiers in Molecular Biosciences, 2021)
Background: Cancer is one of the most deadly diseases at present. Although effective screening and treatment can save lives to a certain extent, our knowledge of the disease is far from sufficient. KIF18B is a member of the kinesin-8 superfamily and plays a conserved regulatory role in the cell cycle. KIF18B reportedly functions as an oncogene in some human cancers, but the correlations between KIF18B and prognosis and immune-infiltrates in different cancers remain unclear. Methods: Data were collected from TCGA, GTEx, CCLE, TIMER, and GSEA databases. The expression difference, survival, pathological stage, DNA methylation, tumor mutation burden (TMB), microsatellite instability (MSI), mismatch repairs (MMRs), tumor microenvironment (TME), immune cell infiltration, and gene co-expression of KIF18B were analyzed using the R language software. Results: KIF18B was widely upregulated in cancers, compared with normal tissues, and high KIF18B expression was associated with unfavorable prognoses. TMB, MSI, MMRs, and DNA methylation correlated with KIF18B dysregulation in cancers. KIF18B correlated closely with tumor immunity and interacted with different immune cells and genes in different cancer types. Conclusions: KIF18B could be used as a prognostic biomarker for determining prognosis and immune infiltration in pan-cancers.